1992
DOI: 10.1080/02681219280000981
|View full text |Cite
|
Sign up to set email alerts
|

Environmental mycology and its importance to public health

Abstract: In this era of the widespread use of broad-spectrum antibiotics, corticosteroids, cytotoxic agents and other immunosuppressants, coupled with the increasingly stressful life styles demanded by modern civilization, it is hard to draw a sharp line between pathogenic and non-pathogenic fungi. Most of the moulds and yeasts, whether primary pathogens, or opportunistic, allergenic or toxigenic fungi, occur in nature as soil-dwelling saprobes or plant pathogens from where they are released into the air. Fungal infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 65 publications
0
30
1
Order By: Relevance
“…Indoor microorganisms may cause health symptoms (Mishra et al, 1992). In the present work the severity of health symptoms was higher among employees at the older library, indoor air quality was worse at the older library.…”
Section: Discussionmentioning
confidence: 59%
“…Indoor microorganisms may cause health symptoms (Mishra et al, 1992). In the present work the severity of health symptoms was higher among employees at the older library, indoor air quality was worse at the older library.…”
Section: Discussionmentioning
confidence: 59%
“…Flannigan, Dutkiewicz et al and Rainer et al declare that fungi present in humid indoor spaces may be responsible for asthma and/or hay fever and alveolitis alergica [25,26,27]. These fungi may also be the cause of immunotoxicity [28,29]. The fungi posing the largest threat to human health and found in the air samples tested were the following species: Aspergillus fumigatus and Aspergillus flavus.…”
Section: Discussionmentioning
confidence: 99%
“…HVAC systems have been associated with increased airborne densities of fungi of various genera, particularly Cladosporium and Penicillium (Hirsch, Hirsch, and Kalbfleisch 1978;Mishra et al 1992). Ahearn et al (1991) reported the colonization of painted metal surfaces of HVAC systems by Cladosporium sp.…”
Section: Growth Of Fungi In Hvac Systemsmentioning
confidence: 99%
“…In such cases, the fungi do not use the metal or concrete for their growth but, rather, use the water and organic debris on the surface, 15 including organics absorbed from the air (Nevalainen 1993;Ahearn et al 1996). Fungi that have been isolated commonly from indoor environments include species of Aspergillus, Penicillium, Cladosporium, Alternaria and Aureobasidium species (Bisett 1987;Nelson et al 1988;Ahearn et al 1991;Mishra et al 1992;Ahearn et al 1992a;. These fungi usually are recovered from sources such as wood rot in domestic interiors, wall coverings, house dust, pets, and houseplants (Mishra et al 1992;Ahearn et al 1992b).…”
Section: { Factors Determining Growth Of Microorganismsmentioning
confidence: 99%